Extraction of Fish Bones Embedded in the Esophagus via Endoscopic Submucosal Dissection: Two Case Reports and Literature Review - Lu, Dan; Lv, Lu; Gu, Qing; Jain, Ajay; Berglund, Björn; Ji, Feng (Frontiers in Medicine, 2021)
Foreign body ingestion is a common problem encountered at gastroenterology clinics and emergency rooms which can cause serious complications. Usually, foreign bodies are directly visible with flexible endoscopes and can be readily removed. However, when foreign bodies migrate into the deeper tissue of the esophagus, surgery is typically required. There is currently no consensus regarding the best treatment. In this report, we present two cases in which fish bones embedded in the muscularis propria of the esophagus were successfully removed via endoscopic submucosal dissection (ESD). Both patients were discharged without any complications.